Consciousness and the mind of God - Taliaferro, Charles (Cambridge University Press, 1994)
Contemporary materialist accounts of consciousness and subjectivity challenge how we think of ourselves and of ultimate reality. This book defends a nonmaterialistic view of persons and subjectivity and the intelligibility of thinking of God as a nonphysical, spiritual reality. It endeavors to articulate in a related way the integral relationship between ourselves and our material bodies and between God and the cosmos.